Experimental and Analytical Investigation of Short Columns with GFRP Bars (International Journal of Innovative Research in Computer Science & Technology, 2022)
Glass fiber reinforced polymer (GFRP)  Rebar ‘s has an innovative material it’s been a potential  application in construction practices due to its high tensile  strength, corrosive resistance ease in its applications and  relatively simple construction technique. To tap such potential, the existing body of knowledge on GFRP must be  expanded to provide a proper basis for officials to add this  method of construction to the provisions of the building  code. This thesis aims to add to that body of knowledge  through experimental investigation on performance of Glass  fibre reinforced bar in compression members. Load carrying capacities of long and short columns  reinforced longitudinally with glass fiber reinforced  polymer rebar and laterally with steel bar were compared  with steel reinforcement in this research. Test series  consisted of columns having 150 Ø mm diameter and 660  mm length of 3 short columns. The main study in this  program is on replacing the longitudinal reinforcement  partially with GFRP bars and cement replaced by 20% with  silica fume. Comparing such differently reinforced column  with fully steel reinforced and GFRP reinforced columns.  Load carrying capacities and failure behaviour of columns  were observed by experimental investigation and compared  with theoretical values. From the obtained results, it is  observed that the replacement in longitudinal reinforcement  partially with GFRP bars in short & long columns show the  higher load carrying capacities. And the failure of the  column is changed for the short columns
Keywords: GFRP bars; silica fume; concrete; replacement